Liquid metal integrated PU/CNT fibrous membrane for human health monitoring - Li, Mei-Xi; Wu, Da-Yong; Tang, Rong-Yu; Zhou, Si-Yuan; Liang, Wei-Hua; Liu, Jing; Li, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Wearable flexible sensors are widely used in several applications such as physiological monitoring, electronic skin, and telemedicine. Typically, flexible sensors that are made of elastomeric thin-films lack sufficient permeability, which leads to skin inflammation, and more importantly, affects signal detection and consequently, reduces the sensitivity of the sensor. In this study, we designed a flexible nanofibrous membrane with a high air permeability (6.10 mm/s), which could be effectively used to monitor human motion signals and physiological signals. More specifically, a flexible membrane with a point (liquid metal nanoparticles)-line (carbon nanotubes)-plane (liquid metal thin-film) multiscale conductive structure was fabricated by combining liquid metal (LM) and carbon nanotubes (CNTs) with a polyurethane (PU) nanofibrous membrane. Interestingly, the excellent conductivity and fluidity of the liquid metal enhanced the sensitivity and stability of the membrane. More precisely, the gauge factor (GF) values of the membrane is 3.0 at 50% strain and 14.0 at 400% strain, which corresponds to a high strain sensitivity within the whole range of deformation. Additionally, the proposed membrane has good mechanical properties with an elongation at a break of 490% and a tensile strength of 12 MPa. Furthermore, the flexible membrane exhibits good biocompatibility and can efficiently monitor human health signals, thereby indicating potential for application in the field of wearable electronic devices.